SEASONAL ABUNDANCE OF CRUSTACEAN COMMUNITY IN A POND ECOSYSTEM OF TR PURAIN RELATION TO PHYSICO-CHEMICAL FACTORS - CHAKRABARTI, SAUMEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The present study was undertaken on a perennial pond ecosystem of Tripura to study the seasonal abundance of crustacean fauna in relation to physico-chemical limnology during a period from March 2012 to February 2013. A total of 18 species of crustacean fauna were recorded and six out of 18 species were numerically dominant. Amongst crustacean fauna, Ceridaphnia reticulata, Diaphanosoma excisium and Chydorus sphaericus dominated in the cladoceran group, Eucyclops agilis and Mesocyclops leuckarti were the dominant copepods while as Cypris sp. was the dominant ostracod. Crustacean community followed a definite rhythm of seasonal abundance showing is ighest density in the summer (Cladocera: 607 ind, /L. Copepoda. 563 indi/L. Ostracoda. 78 indi/L) and lowest in the monsoon (Cladocera: 176 indi/L. Copepoda. 123 indi/L. Ostracoda. 31 indi/L) during study period. Numerical abundance of crustacean fauna was observed in the peripheral zone of aquatic macrophytes. Notable physico-chemical parameters of the studied pond were also observed and their degree of influence over the seasonal abundance of crustacean fauna was noted. The result was evaluated through statistical analysis. Crustacean community when correlated with physico-chemical parameters indicated that the density of crustacean fauna was influenced by physico-chemical parameters of the pond ecosystem.